Content and interpretation of the conceptual apparatus of risk management project - A. V. Pochivalov; A. V. Sysolyatin (Вестник университета, 2021)
One of the important management processes is the identification and management of risks. The article considers the main causes of uncertainty and the occurrence of risk events. The attitude of the authors and standards is presented, the interpretations of the concepts of “risk management” and “risk management” are systematized. The main groups of interpretations of the concept of risk are highlighted, according to which different authors and standards share the concepts. Special attention is paid to the tasks that face the risk management process. A proprietary interpretation of the definition is proposed and justified, taking into account the peculiarities of the risk management process in terms of the stages of risk management, positive and negative consequences, systematic, consistent and cyclical actions in the risk management process in project activities.